2008
DOI: 10.1097/chi.0b013e318185d285
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Abnormalities in Adolescents With Attention-Deficit/Hyperactivity Disorder

Abstract: Objective-Several neuroanatomic abnormalities have been reported in individuals with ADHD. However, findings are not always consistent, perhaps because of heterogeneous subject samples. Studying youths with documented familial ADHD provides an opportunity to examine a more homogeneous population.Method-N=24 youths with a confirmed history of familial ADHD and 10 control youths underwent high-resolution structural Magnetic Resonance Imaging (MRI) examinations. Archived MRI scan data from 12 control youths were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 45 publications
(41 reference statements)
4
18
0
5
Order By: Relevance
“…In addition, covariance analyses revealed that age-adjusted caudate volumes were reduced in the ADHD group, but only for children up to 8.0 years. The current findings are consistent with previous reports in children of a similar age range (Qiu et al, 2009;Tremols et al, 2008) and of a younger age range (Mahone et al, 2011), but opposite to findings in older children (adolescents) with ADHD who displayed larger caudate volumes (Garret et al, 2008). Finally, a positive correlation between age and caudate:cerebrum ratios was present in the younger age subgroup (ADHD and controls combined), indicating that caudate volumes increased with age during this developmental period irrespective of clinical status; this correlation was opposite (negative) in the older age subgroup but only in children with ADHD, indicating a decrease in caudate volumes in the clinical group during this age range.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, covariance analyses revealed that age-adjusted caudate volumes were reduced in the ADHD group, but only for children up to 8.0 years. The current findings are consistent with previous reports in children of a similar age range (Qiu et al, 2009;Tremols et al, 2008) and of a younger age range (Mahone et al, 2011), but opposite to findings in older children (adolescents) with ADHD who displayed larger caudate volumes (Garret et al, 2008). Finally, a positive correlation between age and caudate:cerebrum ratios was present in the younger age subgroup (ADHD and controls combined), indicating that caudate volumes increased with age during this developmental period irrespective of clinical status; this correlation was opposite (negative) in the older age subgroup but only in children with ADHD, indicating a decrease in caudate volumes in the clinical group during this age range.…”
Section: Discussionsupporting
confidence: 91%
“…Different studies have reported that the caudate nuclei of children with ADHD are larger than (Garret et al, 2008;Mataro et al, 1997), smaller than (Castellanos et al, 2003;Hynd et al, 1993;Mahone et al, 2011;Qiu et al, 2009;Semrud-Clikeman et al, 2000) or equal to (Hill et al, 2003) those of normal controls. In addition, the typical asymmetry of the caudate nucleus (right > left) has been reported to be either absent or reversed in children with ADHD (Tremols et al, 2008;Uhlikova et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…A recent DTI study also suggests normalization of the caudate during late adolescence (Silk et al, 2009). This is consistent with findings of increased caudate volume in older adolescents (ages 15 to 19) with ADHD (Mataro et al, 1997; Garrett et al, 2008). Thus, our findings of smaller caudate volumes in children with ADHD are consistent with previous reports in early/mid adolescence, as our subjects had a mean age of 13.4 +/− 3 years.…”
Section: Discussionsupporting
confidence: 91%
“…McAlonan et al (2007) observed deficits within a predominantly right hemispheric frontal-pallidalparietal gray matter network and bilateral white matter tracts in 28 male ADHD children, compared with 31 matched controls. In contrast, in a study of 24 youths with a history of ADHD and 10 healthy age-matched controls, Garrett et al (2008) found similar total cerebral tissue between groups but greater right caudate and right inferior frontal lobe volumes in the ADHD group. Several studies point toward the heritability of frontostriatal structures among ADHD individuals with disruptions in frontostriatal white matter tracts: even after controlling for age, fractional anisotropy in right prefrontal fiber tracts correlated with both functional activity in the inferior frontal gyrus and caudate nucleus, and performance of a go/no go task in parent-child dyads with ADHD (Casey et al 2007).…”
Section: Physical Exercise and Brain Abnormality In Adhdmentioning
confidence: 50%